MENJEMBATANI KESENJANGAN: Menelusuri Dampak Pembangunan Infrastruktur terhadap Ketimpangan Pendapatan di 34 Provinsi Indonesia - Taryn L, Ainaya; Ruthshe, Glori; Lutfiani S, Lia; Anjelika S, Naomi; Tri R, Syarifa (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Indonesia is a country with a population of more than 270 million people, and with an area that stretches from Sabang to Merauke. One of the problems that still occurs is the significant income inequality between urban and rural areas. Equitable infrastructure between urban and rural areas can also be a trigger for income inequality. So, the purpose of this analysis is to see how far the influence of infrastructure equality consisting of road length, electricity use, and consumption of decent drinking water on income inequality in 34 provinces in Indonesia. This study uses quantitative method and by conducting Pooled Least Square Model Regression, Fixed Effect Model (FEM) Regression, and Random Effect Model (REM) Regression, Hausman Test, and Heteroscedasticity Test. This study shows that road length and electricity use are important factors in reducing income inequality, while consumption of safe drinking water is a factor that increases income inequality. Fixed effect model is recommended for analyzing the relationship between road length, electricity use, and drinking water consumption and income inequality.